Evidence, probability and relative plausibility. (October 2022) - Aitken, Colin; Taroni, Franco; Bozza, Silvia
A comparison is made between probability and relative plausibility as approaches for the interpretation of evidence. It is argued that a probabilistic approach is capable of answering the criticisms of the proponents of relative plausibility. It is also shown that a probabilistic approach can answer the problem of overlapping where there is evidence that each side claims supports its theory of what happened.